(3JPcQI GdcMGdjfs - (3GdcMGd , Ydj Hf YjSi GdWHjH GdcMGd,J (B400 (3g` s
(3ChdgG (B:s
(3GdChbGJ Edi GdfXQ ai GdcJH GdcHGQ ai YdGL eQV ef GdCeQGV djSJZfi Hg Yf GdfXQ ai GdcJH GdcHGQ s
(3BNQgG (B:s
(3aEffi GSJYLdJ ai JCdja hLeYg dSQYI MGLJc , aEf cGf Pdc aCUdMg HYO Cf JfYe GdfXQ ajg ,hCf JLYd Ydi ecGaCJi MSf GdOYGA s
(3Vef eLehY , JQJjHgG (B: (3ef U (B126 - (3U(B239s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B49 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs